Increasing biodiesel production yield in narrow channel tubular reactors - Baydır, Enver; Aras, Ömür (Elsevier, 2021)
The purpose of this study is to augment the FAME yield by increasing the contact surface of the reactants that do not mix with each other in continuous biodiesel production. For this aim, many studies have been conducted in the literature and various reactor types have been used (tesla, omega, zigzag, etc.). Especially, the disadvantage of these intensive studies conducted on micro channels is undoubtedly pressure drops. In this study, narrow channel tubular reactors were preferred instead of micro channels, and t-type mixing cells were used to ensure well mixing. Mixing cells of different inner diameters (0.8, 1.2 and 1.5 mm) were adapted to reactors of various diameters (1, 1.5 and 3 mm). Then, the FAME yield was investigated at various catalyst amounts (0.5%, 0.75%, 1%) and residence times (1, 2, 2.5, 3 min). Additionally, it is observed that the percentage of FAME decreased as the residence time increased at smaller reactor diameters and higher catalyst amounts due to basically saponification effect. As a result, it has been shown that the high percentage of FAME, achievable in microchannels in short residence time, can also be achieved in narrow channel reactors with mixing cell assembly.
Keywords: Biodiesel production; Alkaline catalyst; Narrow channel reactor; T type mixing cell; FAME